Effects of emotional stimuli on working memory processes in male criminal offenders with borderline and antisocial personality disorder. (February 2013) - Prehn, Kristin; Schulze, Lars; Rossmann, Sabine; Berger, Christoph; Vohs, Knut; Fleischer, Monika; Hauenstein, Karlheinz; Keiper, Peter; Domes, Gregor; Herpertz, Sabine C.
Abstract Objective. In the present study, we aimed to investigate the influence of concurrently presented emotional stimuli on cognitive task processing in violent criminal offenders primarily characterized by affective instability. Methods. Fifteen male criminal offenders with antisocial and borderline personality disorder (ASPD and BPD) and 17 healthy controls underwent functional magnetic resonance imaging (fMRI) while performing a working memory task with low and high working memory load. In a second experimental run, to investigate the interaction of emotion and cognition, we presented emotionally neutral, low, or high salient social scenes in the background of the task. Results. During the memory task without pictures, both groups did not differ in general task performance and neural representation of working memory processes. During the memory task with emotional background pictures, however, ASPD-BPD subjects compared to healthy controls showed delayed responses and enhanced activation of the left amygdala in the presence of emotionally high salient pictures independent of working memory load. Conclusions. These results illustrate an interaction of emotion and cognition in affective instable individuals with enhanced reactivity to emotionally salient stimuli which might be an important factor regarding the understanding of aggressive and violent behaviour in these individuals.